Oral Candidiasis in Patients with Level CD4+ Below 50 - Cane Lukisari; Kurnia Hayati Rahman; Nafi’ah Nafi’ah; Dwi Setianingtyas; Afryla Femilian (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Approximately 90% of individuals diagnosed with HIV/AIDS have encountered Oral Candidiasis during the progression of their disease, especially in patients with a reduced CD4+ 200 mm3. Oral Candidiasis is a prevalent opportunistic infection of the oral cavity. Reported a case of a patient with oral candidiasis in an HIV/AIDS with CD4+ below 50 and discussed the mechanism of molecular relationship decreasing count CD4+ with virulence of Candida Albicans. In this report, we present a case of a 35-year-old female who presented with oral candidiasis. The patient's CD4+ count test revealed a level below 50 and HIV test I-II-III reactive. Human immunodeficiency Virus causes a decrease in CD4+ count and leads to opportunistic oral candidiasis infection.